The Impact of Ramadan Fasting on Glycemic Stability in Amateur Football Players During the Competitive Phase. - بارودي محمد أمين; مزوز غوثي (Journal of Sport Science Technology and Physical Activities, 2025)
This study evaluated the impact of Ramadan fasting on blood glucose levels in amateur football players during the competitive phase. Using an experimental design, 18 players performed a standardized training session (60% of maximal aerobic speed) before and after the start of Ramadan. Blood glucose was measured using a glucometer before and after training. Statistical analysis showed a significant decrease in glucose levels before training during Ramadan compared to pre-Ramadan levels, followed by an increase afterward. These results indicate that Ramadan fasting affects glycemic stability during training, emphasizing the need for appropriate nutritional and training strategies to maintain performance and health in fasting athletes